The Response of Financial Performance to The Market Power of Islamic Banking in Indonesia - Chajar Matari Fath Mala; Muhammad Nadratuzzaman Hosen; Mohammad Nur Rianto Al Arif (Signifikan: Jurnal Ilmu Ekonomi, 2022)
market power of Islamic banking in Indonesia. This study contributes to filling the gap in the literature by combining the variables under the analysis of impulse response friction (IRF) about the relationship between market power, efficiency, liquidity, profitability, and stability. The data of this study covered Islamic banking in Indonesia from the period January 2010 to 2019 and used IRF from the VAR/VECM panel. This study found that shock/innovation of market power of Islamic banking in Indonesia is responded positively by efficiency, liquidity, and profitability. Meanwhile, financial stability responds negatively to shock/innovation of market power. These findings suggest that innovation in market power in Indonesian Islamic banking will lead to an increase in efficiency, liquidity, and profitability. This result poses a dilemma because competition increases stability but reduces efficiency, liquidity, and profitability. The balance between market power and stability at the macro and industrial levels becomes crucial because it is necessary to maintain the financial system’s stability and national economic growth.How to Cite:Mala, C. M. F., Hosen, M. N., & Al Arif, M. N. R. (2022). The Response of Financial Performance to The Market Power of Islamic Banking in Indonesia. Signifikan: Jurnal Ilmu Ekonomi, 11(2), 415-424. https://doi.org/10.15408/sjie.v11i2.26777.JEL Classification: G18, G21, G28